2006
DOI: 10.1007/s10517-006-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine toxicity in organotypic cultures of rat retina

Abstract: Effects of homocysteine in toxic concentrations on retinal neurons were studied in vitro. In organotypic roller cultures of postnatal (8-12-day-old) and adult rat retina homocysteine caused multiple damage to neurons in the outer nuclear layer, in deep compartments of the inner nuclear layer, and ganglion cell layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Homocysteine may affect retinal cells through increased oxidative stress (Lee et al 2007), and intravitreal homocysteine injections have been shown to be toxic to ganglion-cell neurons (Moore et al 2001). Homocysteine can damage neurons in several layers of rat retina in vitro (Viktorov et al 2006). It can also activate N-methyl-D-aspartic acid (NMDA0 receptors to induce excitotoxic neuronal death in rat retinas (Lipton et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine may affect retinal cells through increased oxidative stress (Lee et al 2007), and intravitreal homocysteine injections have been shown to be toxic to ganglion-cell neurons (Moore et al 2001). Homocysteine can damage neurons in several layers of rat retina in vitro (Viktorov et al 2006). It can also activate N-methyl-D-aspartic acid (NMDA0 receptors to induce excitotoxic neuronal death in rat retinas (Lipton et al 1997).…”
Section: Discussionmentioning
confidence: 99%